Persepsi pasien terhadap mutu pelayanan dalam penerapan patient safety - Dalfian Dalfian; Nova Muhani; Nurul Afiah; Nur Azizah; M Ilham Rivaldi; Dandy Adji Pangestu; Listya Dini (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2022)
Background: Patient safety is the absence of preventable harm to patients during the health care process and the reduction of unnecessary harm associated with health care to a minimum.Patient safety is a framework of organized activities that creates a culture, processes, procedures, behaviors, technologies and environments in health care that consistently and sustainably reduce risk, reduce the occurrence of avoidable hazards, make mistakes less likely and reduce their impact when it happened.Purpose: To determine patients' perception of service quality in the application of patient safety at Pertamina Bintang Amin hospital, Bandar Lampung.Method: A quantitative study using a research design in the form of an analytic survey with a cross sectional approach. The population and samples in this study were patients who were treated in the inpatient unit at hospital.Results: The overall application of patient safety was 58.6% of respondents felt it was good and 41.4% felt it was not good. The ranking of patient safety implementation is good in service units, sequentially from the highest, namely pharmacy services (67.6%), medical services (61.0%), nutritional services (59.0%), laboratory services (58.0%), and radiology services (57.1%). Overall, 66.2% of respondents felt that the quality of service was good and 33.8% felt that it was not good. The ranking of service quality is good in service units based on patient perceptions, sequentially from the highest are medical services (80.0%), nutritional services (69.5%), pharmaceutical services (68.2%), laboratory services (58.0%), and radiology services (53.3%).Conclusion: There is a significant relationship between the application of patient safety to the quality of drug services, pharmacy installation services, nutrition services, laboratory services and radiology services. Keywords: Patients' perception; Service quality; Patient safety; HospitalPendahuluan: Keselamatan pasien adalah kerangka kerja kegiatan terorganisir yang menciptakan budaya, proses, prosedur, perilaku, teknologi dan lingkungan dalam pelayanan kesehatan yang secara konsisten dan berkelanjutan menurunkan risiko, mengurangi terjadinya bahaya yang dapat dihindari, membuat kesalahan lebih kecil kemungkinannya dan mengurangi dampaknya ketika itu terjadi.Tujuan: Untuk mengetahui persepsi pasien terhadap kualitas pelayanan dalam penerapan Patient Safety di RS Pertamina Bintang Amin Bandar Lampung.Metode: Kuantitatif dengan menggunakan rancangan penelitian berupa survei analitik dengan pendekatan cross sectional. populasi dan sampel pada penelitian ini pasien-pasien yang dirawat di unit rawat inap pada Rumah Sakit.Hasil: Penerapan keselamlatan pasien secara keseluruhan sebanyak 58,6% responden merasakan sudah baik dan 41,4% yang mersakan tidak baik. Peringkat penerapan keselamlatan pasien sudah baik pada unit pelayanan berurutan dari tertinggi adalah pelayanan famasi (67,6%), pelayanan pengobatan (61,0%), pelayanan gizi (59,0%),pelayanan laboratorium (58,0%), dan pelayanan radiologi (57,1%). Mutu pelayanan pasien secara keseluruhan, sebanyak 66,2% responden merasakan mutu layanan sudah baik dan 33,8% yang merasakan tidak baik. Peringkat mutu pelayanan sudah baik pada unit pelayanan berdasarkan persepsi pasien secara berurutan dari tertinggi adalah pelayanan pengobatan (80,0%), pelayanan gizi (69,5%), pelayanan farmasi (68,2%),pelayanan laboratorium (58,0%), dan pelayanan radiologi (53,3%).Simpulan: Ada hubungan yang signifikan antara penerapan keamanan pasien terhadap mutu pelayanan obat, pelayanan instalasi farmasi, pelayanan gizi, pelayanan laboratorium dan pelayanan radiologi.